The meat cookbook : know the cuts, master the skills, over 250 recipes - Fletcher, Nichola, 1951- (London : Dorling Kindersley Limited, 2021)
"The ultimate visual course for meat lovers seeking practical information on preparing and cooking meat With this definitive guide to cooking meat, choose the best cuts, perfect your prep, and rustle up delicious dishes with confidence. Discover why cuts matter, how to recognize top-quality meat, why well-raised meat tastes better, and reliable checking methods to know when meat is cooked. Get the best from your meat with step-by-step preparation and cooking techniques, and learn butchery skills you can practise at home. Cook more than 250 of the world's best poultry, pork, beef, lamb, game, and offal dishes such as Jamaican jerk chicken, Portuguese pork with clams, Kerala beef, and saddle of roe venison with celeriac puree. All the recipes include timing and temperature charts for perfect results every time, and there's expert advice on pairing meats with other foods for exciting flavour combinations. Become a master of meat with The Meat Cookbook"--Publisher's description.
Meat know-how -- Poultry -- Pork -- Beef and veal -- Lamb and goat -- Game -- Offal -- Home butchery.
Includes index.
110238
Keywords: Cooking - meat; Identifying cuts - meat; Home butchery - meat; Cookbooks